An ANALYSIS AR-BASED SPEAKING MATERIALS BY IMPLEMENTING PROJECT-BASED LEARNING USING FONDI APPLICATION FOR VISUAL COMMUNICATION DESIGN STUDENTS - Baginda Saeto Gading Dasopang; Nazriani Lubis; Yugi Diraga Prawiyata; Yulia Arfanti (Indonesian Journal of ELT and Applied Linguistics, 2024)
This study aims to develop English-speaking materials based on Augmented Reality (AR) by implementing Project-Based Learning (PjBL) using the Fondi application for tenth-grade Visual Communication Design students at SMK Swasta Istiqlal Delitua. Based on observations and interviews, it was found that students faced difficulties with pronunciation and lacked confidence in speaking English. In addition, the existing learning materials were not tailored to their major and lacked integration with interactive digital media. Through the development of materials aligned with students’ field of study and the use of AR technology and the Fondi application, students expressed high interest in contextual and collaborative learning. The use of AR-based projects and interactive discussions via Fondi encouraged students to be more active, confident, and engaged in real English-speaking practices. The findings indicate that this approach enhances students' motivation and provides a more meaningful and relevant learning experience.